Intra-host diversities of the receptor-binding domain of stork faeces-derived avian H5N1 viruses and its significance as predicted by molecular dynamic simulation - Sukathida Ubol (2018)
Virus evolution facilitates the emergence of viruses with unpredictable impacts on human health. This study investigated intra-host variations of the receptor-binding domain (RBD) of the haemagglutinin (HA) gene of the avian H5N1 viruses obtained from the 2004 and 2005 epidemics. The results showed that the mutation frequency of the RBD ranged from 0.3 to 0.6%. The mutations generated one consensus and several minor populations. The consensus population of the 2004 epidemic was transmitted to the 2005 outbreak with increased frequency (39 and 45%, respectively). Molecular dynamics simulation was applied to predict the significance of the variants. The results revealed that the consensus sequence (E218K/V248I) interacted unstably with sialic acid (SA) with an α2,6 linkage (SAα2,6Gal). Although the mutated K140R/E218K/V248I and Y191C/E218K/V248I sequences decreased the HA binding capacity to α2,3-linked SA, they were shown to bind α2,6-linked SA with increased affinity. Moreover, the substitutions at aa 140 and 191 were positive-selection sites. These data suggest that the K140R and Y191C mutations may represent a step towards human adaptation of the avian H5N1 virus. © 2011 SGM.